The Workers’ Reward at Middleton Hall 1567 - Dawson, Mark (Petits Propos Culinaires, 2010)
The evidence for the ‘feast’ explored in this article is found in the household, personal and estate accounts of the Willoughby family, whose main residences in the sixteenth century were Wollaton Hall, near Nottingham and Middleton Hall in Warwickshire. This paper looks at what workers performing "boon work" (not paid for except by a meal) would have been fed by the gentry who received their assistance on a particular occasion in May 1567.